Estrategias pedagógicas y su influencia en desarrollo de la motricidad gruesa en niños de Educación Inicial II - Cabezas Macias, Ariel Vicente (2025)
Comprehensive development in children of Educación Inicial II is essential for their physical, cognitive, emotional, and social growth. Gross motor skills, including running, jumping, climbing, and balancing, are crucial for fostering independence and body control. However, at Escuela de Educación Básica José Ingenieros, located in Cantón Baba, Los Ríos Province, deficiencies in pedagogical strategies aimed at developing these skills were identified. Data collection was conducted through interviews and observations using a qualitative approach and a non-experimental design. The study involved children from Educación Inicial II and their teachers, with a purposive sample of 33 students and two teachers participating in interviews and direct observations. The expected outcomes include identifying effective teaching strategies and diagnosing key challenges faced by educators. The potential conclusions suggest that enhancing gross motor skills positively impacts not only a child's physical development but also other developmental domains. Additionally, utilizing available resources and implementing innovative methods can significantly improve students' overall well-being.